Do firm failure processes differ across countries: evidence from Finland and Estonia - Laitinen, Erkki K.; Lukason, Oliver (Journal of Business Economics and Management, 2014)
This study considers the novel topic of comparing firm failure processes between different countries. For seventy bankrupt Finnish firms corresponding pairs are found among Estonian bankrupt firms based on industry, size and time of bankruptcy. Despite the similarity of firms from two countries, the analysis shows remarkable differences in both pre-failure financial data and reasons for failure. Based only on financial data, five failure processes are detected for Finnish and six for Estonian firms. Established failure processes associate with different failure reasons. The study contributes to literature by showing that for similar companies failure processes can differ across countries. In practice, the established information about different failure processes can be applied when building or using bankruptcy prediction models.